394. Impact of Misdiagnosis of Clostridioides difficile Infection (CDI) by Standard-of-care Specimen Collection and Testing on Estimates of Hospitalized CDI Incidence Among Adults in Louisville, Kentucky, 2019-2020. (15th December 2022) - Ramirez, Julio A; Angulo, Frederick; Carrico, Ruth; Furmanek, Stephen; Oliva, Senen Pena; Zamparo, Joann M; Gonzalez, Elisa; Zhang, Pingping; Parrish, Leslie Wolf; Marimuthu, Subathra; Pride, Michael W; Gray, Sharon; et al.
Abstract: Background: Public health surveillance indicates that there is a high population-based incidence of laboratory-confirmed hospitalized CDI cases in the United States. Although reported CDI cases are identified via standard-of-care (SOC) specimen collection and CDI testing practices, the impact of SOC misdiagnosis on the reported CDI incidence is uncertain. Methods: Active surveillance from Oct 14, 2019, to Apr 11, 2020, identified inpatients aged ≥50 years with diarrhea (≥3 stools with Bristol score ≥5 in 24 hours) at all wards at 8 of the 9 adult hospitals in Louisville, Kentucky (population > 50 years = 276 456). Study stool specimens from inpatients with diarrhea were screened by rapid GDH/toxin membrane enzyme immunoassay and the positive samples tested by PCR and cell cytotoxicity neutralization assay (CCNA). A study CDI case was a patient with PCR positive/CCNA positive stool or PCR positive stool with pseudomembranous colitis (PMC). Incidence (non-recurrent CDI cases/100 000 persons aged > 50 years per year [PY]) was adjusted for the hospitalization share of participating hospitals and, in a sensitivity analysis, for patients with diarrhea without a CDI test result. SOC stool specimen CDI testing occurred independent of the study. Results: Among 1541 inpatients with diarrhea, study testing identified 109 non-recurrent CDI cases; 18 (16.5%) had PMC, 36 (33.0%) were admitted to intensive care, and 21 (19.3%) died during the 90-day follow-up. Study hospitalized CDI incidence was 154/100 000 PY (202/100 000 PY in the sensitivity analysis). SOC hospitalized CDI incidence was 121/100 000 PY. Of the 109 study CDI cases, 44 (40%) were not SOC-diagnosed (SOC under-diagnosis). Of the 75 SOC CDI cases that also had study testing, 12 (16%) were not study CDI cases (SOC over-diagnosis). SOC-undiagnosed and SOC-diagnosed CDI cases had similar demographics, medical histories, and clinical outcomes. Study testing identified 24% more CDI cases than SOC testing. Conclusion: There was a high incidence of hospitalized CDI in persons aged > 50 years (154-202/100, 000 PY). Of the hospitalized CDI cases, one-third were admitted to ICU and one-fifth died. Public health surveillance estimates of the incidence of laboratory-confirmed hospitalized CDI cases, which are based on SOC testing, may be under-estimated by 24%. Disclosures: Frederick Angulo, DVM PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Joann M. Zamparo, MPH, Pfizer: Employee|Pfizer: Stocks/Bonds Elisa Gonzalez, MPH, Pfizer: Employee|Pfizer: Stocks/Bonds Pingping Zhang, MS, Pfizer: Employee|Pfizer: Stocks/Bonds Michael W. Pride, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Sharon Gray, MPH, Pfizer: Employee|Pfizer: Stocks/Bonds Catia Matos Ferreira, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Forest W. Arnold, DO, MSc, Gilead Sciences, Inc.: Grant/Research Support Raul E. Isturiz, MD, Pfizer: Employee|Pfizer: Stocks/Bonds Nadia Minarovic, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Jennifer Moisi, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Luis Jodar, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds.